Cover Image. (6th April 2020) - Cui, Xiaoyu; Cai, Ruifan; Tang, Xiangjun; Deng, Zhigang; Jin, Xiaogang
Abstract : The cover image is based on the Original Article Sketch‐based Shape‐constrained Fireworks Simulation in Head Mounted Virtual Reality by Xiaogang Jin et al., https://doi.org/10.1002/cav.1920 .